Enhanced European Internet of Things (IoT) Platform Assessment Key Performance Indicators (KPIs) - Nurika, O. (Springer Science and Business Media Deutschland GmbH, 2021)
The current most established IoT platform assessment standard called CREATE-IoT is missing essential KPIs that cover both technical and business aspects. These new KPIs would enhance this standard and improve the quality of assessment outcomes, which eventually would encourage more IoT platform deployments worldwide and open more technology-related jobs that will drive the global economy upward. Through experiences in studying IoT platform technical architecture and business model, this paper formulates and adds 22 unique new KPIs to this standard that initially consists of 198 KPIs. Or conclusively, 11.11 of distinct enhancement has been made. Thus, now this enhanced version of CREATE-IoT assessment standard may cover more IoT platform elements than before. Â© 2021, ICST Institute for Computer Sciences, Social Informatics and Telecommunications Engineering.